2013
DOI: 10.1371/journal.pone.0077258
|View full text |Cite
|
Sign up to set email alerts
|

Thiopental Inhibits Global Protein Synthesis by Repression of Eukaryotic Elongation Factor 2 and Protects from Hypoxic Neuronal Cell Death

Abstract: Ischemic and traumatic brain injury is associated with increased risk for death and disability. The inhibition of penumbral tissue damage has been recognized as a target for therapeutic intervention, because cellular injury evolves progressively upon ATP-depletion and loss of ion homeostasis. In patients, thiopental is used to treat refractory intracranial hypertension by reducing intracranial pressure and cerebral metabolic demands; however, therapeutic benefits of thiopental-treatment are controversially dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 67 publications
(113 reference statements)
0
6
0
Order By: Relevance
“…The activated calmodulin was found to stimulate an adenylyl cyclase as indicated by inhibitor studies with indomethacine as well as several calmodulin blockers 37 all of which block gravitaxis in Euglena . In contrast, forskulin activates the adenylyl cyclase 38 and augments gravitaxis. All these results indicate that the activated calmodulin induces the adenylyl cyclase to produce cyclic adenosine monophosphate (cAMP).…”
Section: Introductionmentioning
confidence: 97%
“…The activated calmodulin was found to stimulate an adenylyl cyclase as indicated by inhibitor studies with indomethacine as well as several calmodulin blockers 37 all of which block gravitaxis in Euglena . In contrast, forskulin activates the adenylyl cyclase 38 and augments gravitaxis. All these results indicate that the activated calmodulin induces the adenylyl cyclase to produce cyclic adenosine monophosphate (cAMP).…”
Section: Introductionmentioning
confidence: 97%
“…This practice is based on numerous reports about the neuroprotective properties of thiopental in the context of neuronal hypoxia/ischemia [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Trifluoperazine and fluphenazin as well as W7 are specific calmodulin inhibitors (Naccache 1985;Russo et al 2014;Son et al 2014) and were found to inhibit gravitaxis in E. gracilis . Likewise, indomethacine impairs the adenylyl cyclase (Wang et al 2012) and decreases the precision of gravitactic orientation in E. gracilis Häder et al 2006), while forskolin activates the adenylyl cyclase (Schwer et al 2013) and augments gravitaxis in Euglena . Phosphodiesterase quenches the cAMP signal (Cai et al 2015).…”
Section: Molecular Biology To Disentangle the Gravitactic Signal Tranmentioning
confidence: 97%